DAMPAK KENAIKAN JUMLAH PENDUDUK TERHADAP TINGKAT PENGANGGURAN TERBUKA DI KOTA SERANG TAHUN 2022-2023 - Maulana, Muhammad Akbar; Kusumoningtyas, Anggi Anggraeni; Hanif, Fahmi Aminatul (Ensiklopedia of Journal, 2025)
This study aims to analyze the impact of population growth on the open unemployment rate in Serang City in 2022-2023. Serang City, as the capital of Banten Province, is experiencing rapid population growth due to urbanization, migration, and birth factors. This growth poses a serious challenge to the open unemployment rate in Serang City. The research method used is quantitative analysis with a descriptive approach. Data were obtained from the Central Statistics Agency (BPS) and other official sources, and analyzed using statistical methods to see the relationship between population growth and unemployment. The results of the study show a positive correlation between population growth and increasing open unemployment rates. Structural unemployment and economic fluctuations also exacerbate this condition, showing that the imbalance between population and job opportunities further exacerbates the unemployment problem. This study makes an important contribution to understanding the impact of demographics on the labor market in Serang City, and offers strategic guidance for local governments in addressing unemployment problems arising from rapid population growth. It is hoped that with the right intervention, the unemployment rate in Serang City can be reduced and community welfare can be increased. Overall, this study makes an important contribution to the understanding of the impact of demographics on the labor market in Serang City, as well as offering strategic guidance for local governments in addressing unemployment problems arising from rapid population growth. Keywords: Population, Welfare, Local Government, Open Unemployment, Workforce